Isolated low-grade serous carcinoma arising in inguinal lymph nodes in the setting of endosalpingiosis: A case report - Samantha A. Solaru; Marisa C. Liu; Vincent Lee; Robert E. Bristow (Gynecologic Oncology Reports)
Introduction: Low-grade serous carcinoma (LGSC) is a rare, indolent subtype of epithelial ovarian cancer that often arises from precursor lesions in the ovary or peritoneum and is associated with MAPK pathway mutations. Unlike high-grade serous carcinoma (HGSC), which typically originates from cells in the fallopian tube, LGSC shows limited response to chemotherapy. An isolated presentation in an extraperitoneal site, such as an inguinal lymph node, is exceedingly rare. We present a case of primary nodal LGSC arising in the setting of endosalpingiosis. Case: An 80-year-old woman presented with a two-year history of left lower quadrant pain and a newly enlarging left groin mass. Imaging identified a vascular left inguinal mass, and initial biopsy favored HGSC. Staging procedures including hysteroscopy, dilation and curettage, and diagnostic laparoscopy with bilateral salpingo-oophorectomy showed normal pelvic organs with no evidence of malignancy. Chemotherapy was initiated but resulted in only a modest response. Surgical resection of the mass itself revealed LGSC with adjacent endosalpingiosis. With no evidence of primary disease elsewhere, a diagnosis of primary inguinal node LGSC arising from endosalpingiosis was made. Conclusion: This case highlights the diagnostic challenges of isolated LGSC without a detectable primary site. Initial misclassification can lead to suboptimal management. Accurate diagnosis requires thorough surgical and pathological evaluation to ensure appropriate treatment in these rare and atypical presentations.